2018
DOI: 10.1007/s00432-018-2765-7
|View full text |Cite
|
Sign up to set email alerts
|

The concept of the okadaic acid class of tumor promoters is revived in endogenous protein inhibitors of protein phosphatase 2A, SET and CIP2A, in human cancers

Abstract: PurposeThe okadaic acid class of tumor promoters, which are inhibitors of protein phosphatases 1 and 2A (PP1 and PP2A), induced tumor promotion in mouse skin, rat glandular stomach, and rat liver. Endogenous protein inhibitors of PP2A, SET and CIP2A, were up-regulated in various human cancers, so it is vital to review the essential mechanisms of tumor promotion by the okadaic acid class compounds, together with cancer progression by SET and CIP2A in humans.Results and discussionThe first part of this review in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Conventional treatment strategies, including surgery, radiotherapy and chemotherapy, are not ideal for its treatment [25]. FTY720 is an immunosuppressive agent and is widely used in the treatment of autoimmune diseases, such as multiple sclerosis, asthma and several kinds of cancers, such as renal cancer, liver cancer and hepatic cancer [26][27][28]. Although many studies have demonstrated its excellent antitumour effects, to our knowledge, there have been no reports about its effect in sacrum chordoma [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional treatment strategies, including surgery, radiotherapy and chemotherapy, are not ideal for its treatment [25]. FTY720 is an immunosuppressive agent and is widely used in the treatment of autoimmune diseases, such as multiple sclerosis, asthma and several kinds of cancers, such as renal cancer, liver cancer and hepatic cancer [26][27][28]. Although many studies have demonstrated its excellent antitumour effects, to our knowledge, there have been no reports about its effect in sacrum chordoma [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is promoted by TGF-β, hepatocyte growth factor (HGF), tumor necrosis factor-α (TNF-α), or hypoxia-inducible factor 1α (HIF1α) [175,176]. In gastric carcinogenesis, Tipα, along with CagA and VacA, plays an underlying role primarily in mucosal damage [177,178].…”
Section: Tumor Necrosis Factor α-Inducing Protein Of H Pylori In Emtmentioning
confidence: 99%
“…Intriguingly, co‐immunoprecipitation assays showed there was an interaction between FOXC1 and three PP2A subunits (Figure D). Moreover, the classical PP2A inhibitor okadaic acid (OA) not only caused an increase in FOXC1 protein level in a dose‐dependent manner (Figure E), but could also maintain FOXC1 protein stability disrupted by treatment with SB203580 (Figure F). To prove whether p38 maintained FOXC1 protein stability through inhibiting ubiquitination, HA‐Ub, Myc‐p38 and FLAG‐FOXC1 were co‐transfected into HEK293 cells to perform co‐immunoprecipitation assays with anti‐FLAG.…”
Section: Resultsmentioning
confidence: 99%